Putting Tanzania's Hidden Economy to Work : Reform, Management, and Protection of its Natural Resource Sector - World Bank (Washington, DC : World Bank, 2012)
This paper tells a story about conditions in Tanzania's hidden economy, the parts of the natural resource sector often ignored in conventional economic analyses and studies, and makes recommendations for future policy actions. The paper draws primarily from extensive background studies undertaken of the forestry, fishery, wildlife, mining, and tourism sub sectors (COWI 2005) as well as a wide range of complementary studies undertaken by the World Bank and others. It de-emphasizes those sectors with factors of production that are not readily traded or exported (such as land and water), although some examples are given relating to soil quality and water management based on extensive studies undertaken within the agriculture and water sectors. The story is relatively simple: pricing distortions, coupled with institutional weakness and the lack of rule of law, have created an environment that undermines economic growth. This paper also acknowledges that Tanzania has already taken positive steps to making some of the needed corrections to protect its natural resources. In recent analyses of corruption indicators world-wide (World Bank Institute 2006), Tanzanian stands out among those nations as having made significant progress towards improving accountability and reducing economic leakages. Anti-corruption legislation was drafted for parliament attention in early 2007. Revisions to the Deep Sea Fishing Authority Act were passed into law in early 2007. Moreover, changes in institutional arrangements, taxation, and general management of the resource sector show promise and have contributed positively to general economic growth. Yet, the sector remains fragile and vulnerable in other respects: perceptions of unequal income distribution, impacts of climate change, and other external influences must also be addressed to build on past successes.